Translating Epistemic Adverbs from English into Spanish: Evidence from a Parallel Corpus - Ramón, Noelia (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2009)
AbstractThe expression of modal meanings is an area of great complexity in the relationship between form and function in a single language and cross-linguistically. Modal adverbs in particular are considered to be problematic from a contrastive perspective due to their multifunctionality in English (Aijmer 2005). This paper is a corpus-based study of the expression of epistemic possibility by means of three common modal adverbs in English (certainly, probably, possibly) and the translational options chosen in Spanish for expressing those meanings. The aim is to identify trends in the translations of these epistemic adverbs that contribute to a better understanding of the various semantic functions that native speakers attribute to these units. The analysis shows that the omission of modal adverbs in the translations may be considered as an indicator of the degree of grammaticalization attained by these adverbs in English. The results provide useful information not only in the field of translator training and practice, but also in descriptive linguistics.